Особливості та економіка електронної торгівлі: досвід для України в умовах економічної нестабільності - Prokopets, Liudmyla; Куцька, Катерина; Залецька, Інна; Головчак, Юрій (My University, 2023)
У статті досліджено актуальну проблему особливостей електронної торгівлі в умовах економічної нестабільності в Україні. Політична нестабільність може мати далекосяжні наслідки для економічної діяльності будь-якої країни. Автори цієї статі мають на меті проаналізувати особливості розвитку електронної торгівлі, зосередившись на прикладі ринку України, найбільшої у Європі держави із величезним потенціалом у сфері діджиталізації, яка функціонує у дуже нестабільній економіко-політичній площині. Дослідження базувалося на розкритті сутності електронної торгівлі, визначенні економіко-політичних чинників, що негативно впливають на суб’єктів цієї галузі. Розроблено авторську схему ризиків та можливостей впливу дестабілізувальних факторів на сферу електронної торгівлі. А також запропоновані практичні рекомендації, щоб підвищити ефективність від електронної діяльності.
Features and economics of e‐commerce: experience for Ukraine in conditions of economic instability
Economy and politics are two subsystems of a single social system. They are interconnected because they are the subject of the interests of various industries and the same people − the realization of these interests occurs through the appropriate form of interaction, distribution and redistribution of economic and political power. Economic and political instability is caused by external and internal factors. The main external factors of recent years are the Covid-19 pandemic and russia's war against Ukraine. In modern conditions, the problem of economic and political changes in Ukraine is gaining special relevance. Undoubtedly, all these negative phenomena affect e-commerce as a separate sphere of the economy. The pandemic has not only affected the economy in 2021, but has also increased the level of uncertainty about the political conditions for companies to operate. Governments quickly developed policy measures to respond to the pandemic, including by applying innovative solutions. The uncertainty associated with these sudden changes in policy in almost all countries has made it difficult for companies to develop and implement their strategy. Therefore, it is very important for businesses to actively monitor economic and political risks in order to identify both potential problems and opportunities that may arise in the coming years. The pandemic brought negativity into our lives: a large number of sick people, deaths, closure of offline businesses, but a huge positive phenomenon was the active development of online businesses.The rapid development of information and communication technologies, as well as the increase in the use of the Internet, have led to innovations in all aspects, including the e-commerce. The purpose of the study was to study the essence of electronic commerce, the determination of economic and political factors that negatively affect the subjects of this industry. An author's scheme of risks and opportunities for the influence of destabilizing factors on the field of electronic commerce was developed. And a number of practical recommendations are given to increase the effectiveness of electronic activities.
Keywords: електронна торгівля; цифрова економіка; дестабілізувальні фактори; політична нестабільність